#### Answer

$-2\sqrt[3] 4$

#### Work Step by Step

$\sqrt[3] {-32}=\sqrt[3] {-8\times4}=\sqrt[3] {-8}\sqrt[3] 4=-2\sqrt[3] 4$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-2\sqrt[3] 4$

$\sqrt[3] {-32}=\sqrt[3] {-8\times4}=\sqrt[3] {-8}\sqrt[3] 4=-2\sqrt[3] 4$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.